Classification of Sciences: A Comparative Study of Iḥyā’ ‘ulūm aI-dīn and al-Risālah al-laduniyyah - Sa’ari, Che Zarrina (Intellectual Discourse, 1999)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--> Al-Ghazālī expressed many ideas on the theory of knowledge in his different works including Iḥyā’ ‘ulūm aI-dīn as well as al-Risālah al-laduniyyah. The former work is accepted by the scholars as securely attributed to al-Ghazālī, while the authenticity of the latter has been questioned by them. This article tries to compare al-Ghazālī’s views on the classification of sciences between the theory revealed in these two works to show their similarities and differences. In order to assess the mentioned purpose, this article attempts to divide the sciences explained in the Iḥyā’ and the Risālah into three different but linked categories, i.e., sciences which “come upon one” (ḥuḍūriyyah) and sciences which are acquired (ḥuṣuliyyah); revealed (shar‘iyyah) and rational (‘aqliyyah) sciences; theoretical (nazariyyah) and practical (‘amaliyyah) sciences. This article argues that both works have similarities as well as differences.